Potensi Senyawa Aktif Minyak Atsiri Kulit Kayu Manis sebagai Agen Pengusir Tikus (Rodent Repellent): Literature Review - Rodifah Royan (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Cinnamon (Cinnamomum spp.) bark essential oil contains bioactive compounds—primarily trans-cinnamaldehyde and eugenol that show broad-spectrum biological activity. Rodents (Order Rodentia) pose persistent threats to human food security, public health, and household safety. Conventional rodent control relies heavily on synthetic rodenticides, which carry risks of non-target toxicity, environmental persistence, and human poisoning. Herbal repellents, by contrast, deter rodents through olfactory and gustatory cues without killing them, making them a safer and more ecologically sound alternative. This literature review aims to evaluate the scientific evidence on the potential of essential oil from cinnamon bark as a rodent repellent (rodent repellent) agent. A systematic search of primary peer-reviewed journals published between 2019 and 2026 was conducted. The reviewed evidence indicates that trans-cinnamaldehyde, the dominant constituent of cinnamon bark essential oil, elicits strong repellent responses in a range of arthropod and rodent pest species through mechanisms including olfactory receptor activation, acetylcholinesterase disruption, and ionotropic receptor binding. Formulation strategies such as nanoemulsions, chitosan nanoparticles, and gel matrices significantly enhance repellent efficacy and durability. The findings support the conclusion that cinnamon bark essential oil is a scientifically promising, biodegradable, and low-toxicity candidate for herbal rodent repellent development, warranting further in vivo bioassay and field evaluation specifically targeting rodent species.